2016
DOI: 10.1007/s00382-016-3094-7
|View full text |Cite
|
Sign up to set email alerts
|

Energetics and monsoon bifurcations

Abstract: monsoon over India. The default model with mean parameter estimates does not contain a bifurcation, but the model admits bifurcation as parameters are varied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…As we noted earlier, Boos and Storelvmo (2016a) reported that a bifurcation was seen in their model only when a dominant term in the thermodynamic balance, the dry thermal stratification, was ignored. Consistent with this result is the study of Seshadri (2017), which pointed out that bifurcation arose in the simple models of (Levermann et al, 2009) owing to the neglect of the static stability of troposphere. Seshadri (2017) showed that dry thermal stratification provided a stabilizing effect in the energy balance, which exported dry static energy through a term that is linear in the wind-speed.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…As we noted earlier, Boos and Storelvmo (2016a) reported that a bifurcation was seen in their model only when a dominant term in the thermodynamic balance, the dry thermal stratification, was ignored. Consistent with this result is the study of Seshadri (2017), which pointed out that bifurcation arose in the simple models of (Levermann et al, 2009) owing to the neglect of the static stability of troposphere. Seshadri (2017) showed that dry thermal stratification provided a stabilizing effect in the energy balance, which exported dry static energy through a term that is linear in the wind-speed.…”
Section: Introductionmentioning
confidence: 55%
“…Consistent with this result is the study of Seshadri (2017), which pointed out that bifurcation arose in the simple models of (Levermann et al, 2009) owing to the neglect of the static stability of troposphere. Seshadri (2017) showed that dry thermal stratification provided a stabilizing effect in the energy balance, which exported dry static energy through a term that is linear in the wind-speed. In contrast, the stabilizing effect in the absence of this stratification is much weaker, relying on horizontal advection and thus depending quadratically on wind-speed.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Further analysis by Schewe et al (2012) suggested that the nonlinear transitions in monsoons could occur on account of a specific humidity threshold due to complex moisture advection feedbacks. Boos and Storelvmo (2016) and Seshadri (2017) criticized the simple model since it did not accurately represent the dominant balance of the dry static energy budget in tropical atmosphere. Boos and Storelvmo (2016) used a global model to show that the Asian monsoon responds linearly to wide variety of radiative forcing.…”
Section: Discussionmentioning
confidence: 99%
“…This uncertainty in future projections raises questions about potential mechanisms of change that may be present in some models but not others, and that may be responsible for the large differences between models. In particular, paleoclimatic records suggest that Sahel rainfall is capable of abrupt transitions in response to gradual forcing (DeMenocal et al, 2000;McGee et al, 2013); and theoretical studies have demonstrated that such a non-linear response can in principle arise from internal monsoon dynamics (Levermann et al, 2009;Seshadri, 2016). In this study, we examine Sahel rainfall in state-of-the art climate model simulations and show that in those models that exhibit the strongest rainfall increase, this increase is non-linearly related to the SST warming in the tropical North Atlantic and Mediterranean moisture source region.…”
mentioning
confidence: 99%